Azacitidine improves outcome in higher‐risk MDS patients with chromosome 7 abnormalities: a retrospective comparison of GESMD and GFM registries. (2nd April 2018) - Díez‐Campelo, María; Lorenzo, Jose I.; Itzykson, Raphael; Rojas, Silvia M.; Berthon, Céline; Luño, Elisa; Beyne‐Rauzy, Odile; Perez‐Oteyza, Jaime; Vey, Norbert; Bargay, Joan; Park, Sophie; Cedena, Teresa; et al.
Summary: Treatment with azacitidine (AZA) has been suggested to be of benefit for higher‐risk myelodysplastic syndrome (HR‐MDS) patients with chromosome 7 abnormalities (Abn 7). This retrospective study of 235 HR‐MDS patients with Abn 7 treated with AZA ( n  = 115) versus best supportive care (BSC; n  = 120), assessed AZA treatment as a time‐varying variable in multivariable analysis. A Cox Regression model with time‐interaction terms of overall survival (OS) at different time points confirmed that, while chromosome 7 cytogenetic categories (complex karyotype [CK] versus non‐CK) and International Prognostic Scoring System risk (high versus intermediate‐2) retained poor prognosis over time, AZA treatment had a favourable impact on OS during the first 3 years of treatment compared to BSC (Hazard ratio [HR] 0·5 P  < 0·001 at 1 year, 0·7 P  = 0·019 at 2 years; 0·73 P  = 0·029 at 3 years). This benefit was present in all chromosome 7 categories, but tended to be greater in patients with CK (risk reduction of 82%, 68% and 53% at 1, 3 and 6 months in CK patients; 79% at 1 month in non‐CK patients, P  < 0·05 for all). AZA also significantly improved progression‐free survival ( P  < 0·01). This study confirms a time‐dependent benefit of AZA on outcome in patients with HR‐MDS and cytogenetic abnormalities involving chromosome 7, especially for those with CK.